1967
DOI: 10.1111/j.1365-2621.1967.tb01946.x
|View full text |Cite
|
Sign up to set email alerts
|

The Histology of Pre‐Rigor and Post‐Rigor Ox Muscle Before and After Cooking and Its Relation to Tenderness

Abstract: SUMMARY—Pre‐rigor and post‐rigor semitendinosus muscle was examined under the light microscope and in the electron microscope before and after cooking. During cooking, pre‐rigor samples were unrestrained or restrained on stainless‐steel frames at normal length and at 130% normal length. Samples which passed at 0°C into rigor unrestrained, or while restrained to the same degrees of stretch as above, were cooked post‐rigor without mechanical restraint after various periods of storage. The treatments produced dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 11 publications
3
13
0
Order By: Relevance
“…In Hanwoo, one significant GO term was ‘regulation of actin filament length related to muscle metabolism’ (GO:0030832, p-value = 0.044), including actin-related protein 3 homolog ( ACTR3 ), actin-related protein 2/3 complex, subunit 2 ( ARPC2 ), villin 1 ( VIL1 ), and destrin ( DSTN ) genes. Meat tenderness is generated by the disruption of actin filaments and by breaking down the interaction between the actin and myosin filaments [26]. Notably, a significant GO term of ‘striated muscle cell differentiation’ (GO:0051146, p-value = 0.034) was found in Holstein, including the retinoid X receptor, alpha ( RXRA ) gene, which inhibits adipogenesis [27] and plays a negative role in marbling in Hanwoo [28].…”
Section: Resultsmentioning
confidence: 99%
“…In Hanwoo, one significant GO term was ‘regulation of actin filament length related to muscle metabolism’ (GO:0030832, p-value = 0.044), including actin-related protein 3 homolog ( ACTR3 ), actin-related protein 2/3 complex, subunit 2 ( ARPC2 ), villin 1 ( VIL1 ), and destrin ( DSTN ) genes. Meat tenderness is generated by the disruption of actin filaments and by breaking down the interaction between the actin and myosin filaments [26]. Notably, a significant GO term of ‘striated muscle cell differentiation’ (GO:0051146, p-value = 0.034) was found in Holstein, including the retinoid X receptor, alpha ( RXRA ) gene, which inhibits adipogenesis [27] and plays a negative role in marbling in Hanwoo [28].…”
Section: Resultsmentioning
confidence: 99%
“…1956;Hostetler and Cover 1961), the larger extensibility in prerigor cooked meat is consistent with its toughness (Dransfield and Rhodes 1975). Although, surprisingly, little differences in light microscopy structure is seen in the bolus formed after chewing tough or tender meats (Weidemann et al 1967).…”
Section: Discussionmentioning
confidence: 68%
“…Rapid heating early prerigor would give tender meat of high pH (Dransfield and Rhodes 1975) and would not be comparable to heating at later times when the pH is about 5.5. Using this slow heating, there were no gross distortions and dense contraction bands as is obtained by rapid heating of nonrestrained prerigor beef muscle (Weidemann et al 1967). Intramyofibrillar splitting is observed with rapid heating but not with slow heating of prerigor beef (Hericher et al 1988).…”
Section: Discussionmentioning
confidence: 93%
“…Cooked prerigor meat has been found to be more tender than cooked postrigor meat Paul et al 1952;Pearson 1971). Weidemann et al (1967) found that after broiling and oven roasting, prerigor muscle became more tender product and postulated that the production of supercontraction clots disrupted the protein filaments and produced the resulting tenderization. cooked sternomandibularis muscle at various stages of rigor mortis and concluded that although prerigor muscles shortened considerably more than postrigor muscle, cooking losses for prerigor muscle were lower and tenderness ratings were higher, particularly if cooked within 3 hr of slaughter.…”
Section: Cooking Prerigor Musclementioning
confidence: 99%
“…Weidemann et al (1967) found that after broiling and oven roasting, prerigor muscle became more tender product and postulated that the production of supercontraction clots disrupted the protein filaments and produced the resulting tenderization. They also observed the clots of coagulated proteins in cooked prerigor beef as observed by Weidemann et al (1967) and suggested that these clots were an indication of a disruption of the muscle's internal structure. The speed of heat application of microwave cookery could, perhaps, produce even better tenderization results than conventional methods of cookery (Streitel et al 1977).…”
Section: Cooking Prerigor Musclementioning
confidence: 99%